Aging-related NADPH diaphorase positive neurodegenerations in the sacral spinal cord of aged non-human primates - Yinhua Li; Zichun Wei; Yunge Jia; Wei Hou; Yu Wang; Chenxu Rao; Ximeng Xu; Hang Li; Jingjing Sun; Shun Yu; Geming Shi; Guanghui Du; et al. (Scientific Reports, 2024)
Abstract Nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) was used to detect neurodegenerations in aged monkeys. Our previous studies have shown that aging-related NADPH-d positive bodies (ANBs) and megaloneurites appeared in the lumbosacral spinal cord of aged rats and dogs, respectively. To determine the occurrence of megaloneurites and ANBs in non-human primates, we used NADPH-d histochemistry to perform an advanced study of aging-related alterations in aged male monkeys. We identified two distinct abnormal NADPH-d positive alterations, which were expressed as ANBs and megaloneurites, mainly distributed in the superficial dorsal horn, dorsal gray commissure, lateral collateral pathway (LCP) and sacral parasympathetic nucleus of the sacral spinal cord in aged monkeys. Meanwhile, large diameter punctate NADPH-d abnormalities occurred and scattered in the lateral white matter of the LCP and dorsal root entry zone at the same level of megaloneurites in the gray matter. Immunohistochemical results showed that megaloneurites and ANBs are two distinct abnormal alterations, with megaloneurites co-localizing with vasoactive intestinal peptide immunoreactivity, whereas ANBs were not co-localized. Both ANBs and megaloneurites provide consistent evidence that the anomalous NADPH-d alterations in the aged sacral spinal cord are referred to as a specialized aging marker in the pelvic visceral organs in non-human primates.